A new technique for characterization of digital-to-analog converters in high-speed systems - Savoj, Jafar; Abbasfar, Ali-Azam; Amirkhany, Amir; Garlepp, Bruno W.; Horowitz, Mark A. (2007 Design, Automation & Test in Europe Conference & Exhibition : Nice, France, 16-20 April 2007, 2007)
In this paper, a new technique for characterization of digital-to-analog converters (DAC) used in wideband applications is described. Unlike the standard narrowband approach, this technique employs Least Square Estimation to characterize the DAC from dc to any target frequency. Characterization is performed using a random sequence with certain temporal and probabilistic characteristics suitable for intended operating conditions. The technique provides a linear estimation of the system and decomposes nonlinearity into higher-order harmonics and deterministic periodic noise. The technique can also be used to derive the impulse response of the converter, predict its operating bandwidth, and provide far more insight into its sources of distortion.